Mapping the hyaluronan-binding site on the link module from human tumor necrosis factor-stimulated gene-6 by site-directed mutagenesis. - Mahoney, D; Blundell, C; Day, A (2001)
Link modules are hyaluronan-binding domains found in extracellular proteins involved in matrix assembly, development, and immune cell migration. Previously we have expressed the Link module from the inflammation-associated protein tumor necrosis factor-stimulated gene-6 (TSG-6) and determined its tertiary structure in solution. Here we generated 21 Link module mutants, and these were analyzed by nuclear magnetic resonance spectroscopy and a hyaluronan-binding assay. The individual mutation of five amino acids, which form a cluster on one face of the Link module, caused large reductions in functional activity but did not affect the Link module fold. This ligand-binding site in TSG-6 is similar to that determined previously for the hyaluronan receptor, CD44, suggesting that the location of the interaction surfaces may also be conserved in other Link module-containing proteins. Analysis of the sequences of TSG-6 and CD44 indicates that the molecular details of their association with hyaluronan are likely to be significantly different. This comparison identifies key sequence positions that may be important in mediating hyaluronan binding, across the Link module superfamily. The use of multiple sequence alignment and molecular modeling allowed the prediction of functional residues in link protein, and this approach can be extended to all members of the superfamily.